Reading ability of young school-age children - Mile Vuković; Rada Reljić Trivković; Slađana Ćalasan (Биомедицинска истраживања, 2022)
Introduction: . Reading is a complex linguistic and cognitive ability, acquired through learning. Children of typical development in the first four years of school completely master the reading skill. Howev er, some children may have difficulty learning to read despite their preserved intellectual abilities and adequate training. The aim of this paper is to determine the reading ability and to identify reading dis order in children of younger school age. Methods: . The sample consisted of 123 students of third, fourth and fifth grade of elementary school. The three-dimensional reading test - the text "One Snowy Day" was used. Reading speed, reading accura cy and reading comprehension were assessed. Results: . Slow reading was identified in 35.3% of third graders and 22.2% of fourth graders. Deficits in reading accuracy were observed in 8.8% of third grade students. Delays in the development of reading comprehension were identified in most of the examined students. On the whole, our results showed that there is no statistically signifi cant difference in reading ability between boys and girls. Conclusion: . A significant number of children is late in mastering reading skills. Given that reading speed increases significantly with age, and the number of errors decreases, we expect that many slow readers will reach an appropriate reading speed, and that most of the children who showed unexpected number of errors will master accu rate word decoding. Since comprehension deficits were identified in the majority of respondents, we conclude that a significant number of children did not reach the developmental stage in which reading becomes a means of learning.
Keywords: reading; reading speed; accuracy in reading; reading comprehension; young school age